UPAYA PENINGKATAN KETERAMPILAN MENULIS KARANGAN SEDERHANA MELALUI GAMBAR SERI PADA SISWA KELAS III SD NEGERI TUMBANG BARINGEI 1 DENGAN MEMANFAATKAN ALAT PERAGA PEMBELAJARAN TAHUN PELAJARAN 2018 / 2019 - Bisie (Pahlawan, 2021)
Teaching Indonesian in elementary schools focuses on language skills. As we all know, language skills are divided into 4 aspects, namely listening, reading, writing, and speaking. Although each has its own characteristics and peculiarities, the four aspects of language skills have an integral relationship and cannot be separated.Writing, which is one aspect of language, seems to be an obstacle for most elementary school children. Whereas writing skills for elementary school children should be given from an early age. Theory and writing techniques should have been introduced and applied since the lower grades. To anticipate the difficulties experi-enced by students in developing writing skills, on this occasion, I will conduct a class action research, as a fol-low-up in improving learning. Based on the results of data collection and study of pedagogic theories contained in research activities, it turns out that the use of media or teaching aids in learning becomes the most influential element in helping optimize students' thinking. It can be seen from the results of the study which showed that the ability of students to express their ideas in the form of simple essays increased further after the improvement of learning activities by diversifying learning media.